Sarcopenia is associated with an increased inflammatory response to surgery in colorectal cancer. Issue 4 (August 2016) - Reisinger, Kostan W.; Derikx, Joep P.M.; van Vugt, Jeroen L.A.; Von Meyenfeldt, Maarten F.; Hulsewé, Karel W.; Olde Damink, Steven W.M.; Stoot, Jan H.M.B.; Poeze, Martijn
Summary: Background & aims: Sarcopenia in gastrointestinal cancer has been associated with poor clinical outcome after surgery. The effect of low muscle mass on the inflammatory response to surgery has not been investigated, however skeletal muscle wasting in the context of cachexia is associated with a hyperinflammatory state at baseline. Knowledge on this matter can provide new insight into the detrimental effects of sarcopenia on postoperative recovery, possibly leading to novel therapeutic strategies. The aim of this study was to evaluate whether low muscle mass is associated with increased inflammation after resection of colorectal malignancies. Methods: Eighty-seven consecutive patients undergoing elective resection of a primary colorectal tumor were enrolled. Muscle mass was assessed on routine preoperative computed tomography (CT) scans using image analysis by Osirix ® by measuring skeletal muscle at the third lumbar vertebra (L3) level. The effect of muscle mass on pre- and postoperative plasma concentrations of C-reactive protein (CRP), calprotectin and interleukin-6 (IL-6) was analyzed. Clinical outcome was assessed by HARM (HospitAl stay, Readmission, and Mortality) scores. Results: Skeletal muscle mass was not predictive of plasma concentrations of CRP and IL-6. However, low skeletal muscle mass was significantly predictive of high plasma concentrations of calprotectin on postoperative days (POD) 2 through 5, reaching highest significance on POD4 (regression beta,  −6.06; 95% confidence interval,  −10.45 to −1.68; p  = 0.007). Conclusions: Low muscle mass in patients undergoing surgery for colorectal cancer was associated with an increased postoperative inflammatory response. This may be at least part of the explanation for the high incidence of postoperative complications in sarcopenic patients.